Peningkatan Kompetensi Profesional Guru Melalui Penguatan Efikasi Diri Dan Komitmen Profesi Guru - Nur Aini Chasanah; Griet Helena Laihad; Eri Sarimanah (Universitas Pakuan, 2023)
INCREASING TEACHER PROFESSIONAL COMPETENCE THROUGH STRENGTHENING SELF-EFFICACY AND TEACHER PROFESSIONAL COMMITMENT (RESEARCH ON PUBLIC ELEMENTARY SCHOOL TEACHERS IN SOUTH BOGOR DISTRICT, BOGOR CITY USING CORRELATION ANALYSIS AND THE SITOREM METHOD)This study aims to find efforts to improve teacher performance by strengthening the variables that are related to This study aims, in general, to improve the professional competence of teachers in public elementary schools teachers in South Bogor District, Bogor City, through efforts to develop the variables of self-efficacy and professional commitment, namely by identifying the strengths of the relationship between these variables. The population in this study was 398 civil servant teachers from 38 public elementary schools in South Bogor District, Bogor City. The sampling technique used in this research is multistage proportional random sampling, which is taking a random sample of the population proportionately. Determination of the proportion of the study population, namely teachers in public elementary schools by 43% from 398 teachers to 170 teachers (rounding), the proportion in each public elementary school in South Bogor District, Bogor City, is the same as the initial distribution, determining the number of samples using the Slovin formula so that 120 are obtained, people. Data were collected using questionnaires and written tests (for professional competency improvement variables) which had been tested for validity and reliability. The results of the study concluded: 1) There is a positive and significant relationship between self-efficacy and the professional competence of teachers. The correlation value ry1 is 0.658, with the strength of the relationship in the category of strong. 2) There is a positive and significant relationship between professional commitment and teacher professional competence; the ry2 correlation value is 0.675 with strong criteria. 3) There is a positive and significant relationship between self-efficacy and professional commitment together with the teacher's professional competence. The correlation value ry12 is 0.756, which means that the relationship is strong